Do mandibular complete dentures made using a neutral zone technique improve speech?—A pilot study. (26th July 2017) - Rehmann, Peter; Künkel, Anna Katharina; Weber, Daniel; Lotzmann, Ulrich; Wöstmann, Bernd
Abstract : Objective: The aim of this study was to evaluate speech sound production (SSP) in older edentulous patients provided with two different types of mandibular complete dentures (MCDs; conventional vs neutral zone). Background: Regarding the fact that complete dentures (CDs) affect SSP, it is unknown whether the set‐up of the artificial teeth resulting from the neutral zone technique leads to a negative impact on SSP. Materials and methods: For 21 participants, a conventional MCD and a MCD using a modified neutral zone technique (neutral zone dentures) were fabricated. The SSP was described using a phonetically balanced text, which was recorded digitally and evaluated. Results: No significant difference in SSP was observed. Conclusion: Within the limits of this study, it can be concluded that the application of the neutral zone technique in the mandible has no considerable impact on SSP.